The Analysis of Cases Under Suspicion of Anal Sexual Assault in Kahramanmaraş Between 2005 and 2007 - Karanfil, Ramazan; Toprak, Sadık; Arslan, Muhammet Mustafa (The Bulletin of Legal Medicine, 2008)
Even though the majority of sexual assault victims are women, such assaults against men are also seen. In cases concerning children, male subjects can particularly be the target of sexual assault. Besides, anal region can be chosen as the target for sexual assault. The aim of this study is that showing of demographics of anal sexual assault cases and discussion of physical signs under the light of literature. The cases under suspicion of anal sexual assault and examined in our clinic between January 2005 and December 2007 Kahramanmaraş region were included into the study and a form was filled in a face to face meeting. Cases were analysed with their examination findings. 101 (81,5 %) female and 23 (18,5 %) male cases, total 124 cases, were examined at this period. Among these cases, 36 cases were under suspicion of anal sexual assault and 33.3 % of them were male and 66.7 % of them were female, also there were physical signs in 44.4 % of cases. Cases under 12 years of age were mostly male (8 out of 11 cases). However, cases older than 12 years age were mostly female. Perpetrators were from the same environment or close family members in 94.4 % of cases. Examination were done in first three days. The most common place was a house that was unknown by victims in 27.8 % of cases. The study demonstrated, in order to help victims and get better judicial service, sexual assault victims should be examined by a forensic medicine specialists as soon as possible.Key words: Sexual assault, anus, penetration
Keywords: sexual assault; anus; penetration